Chinese writing in English: nation, representation, and identity in Chinese immigrant writers' literature,1980-2020 - Lu, Qianting (Nanyang Technological University, 2023)
Since the late 1980s, Chinese immigrant writers’ representations of China have been credited with “authenticity”, which functions as a window for the English-speaking world to understand the history, culture, and politics of contemporary Chinese society. Because of these writers’ decision to write in English, their works are often assimilated into the literature of ethnic minorities in the host country and merged into genres like Chinese American literature or Chinese British literature. However, the intersectional space that these immigrant writers inhabit in relation to language, culture, and identity has inspired me to investigate the seeming plausible “authority” that they obtain in representing China. Indeed, in comparison to Chinese American writers, whose narratives about China are often questioned on the basis of their reliability, writers from mainland China often earn greater credibility with far less effort. Therefore, this thesis focuses on the pivotal concerns of language, identity, and representation, tackling their inextricable relations with the nation and the concept of “Chineseness”. By investigating the representations of China constructed by Chinese immigrant writings from 1980 to 2020, the thesis identifies three waves of Chinese writers in English, marked by historical turning points that inspire their dedication to writing literature in English, namely: the conclusion of the Cultural Revolution in 1976; the Tiananmen Protest in 1989; and the influence of globalization after 2000. These key historical moments permeate through each wave and emphasize both continuity and discontinuity between their generational representations.